The Influence Of Human Resource Quality And Work Commitment On Employee Performance At CV. Wirabuana Tasikmalaya - Rezeki, Mila Sri; Karmila, Mila; Barlian, Barin (Universitas Dehasen Bengkulu, 2024)
The purpose of this research is to determine and analyze the influence of human resource quality, work commitment on CV employee performance. Wirabuana Tasikmalaya. The research method used is a quantitative research method. The objects of this research are CV employees. Wirabuana Tasikmalaya, with a sampling technique using the saturated sampling method. The data analysis technique used is multiple linear regression analysis. Based on the research results, it is known that there is a significant simultaneous influence between the Quality of Human Resources and Work Commitment on Employee Performance. Quality of Human Resources partially has no significant effect on Employee Performance and Work Commitment partially has a significant effect on Employee Performance of CV Wirabuana Tasikmalaya.